Kras, Egfr, and Tp53 Mutations in B6C3F1/N Mouse and F344/NTac Rat Alveolar/Bronchiolar Carcinomas Resulting from Chronic Inhalation Exposure to Cobalt Metal. (August 2015) - Hong, Hue-Hua L.; Hoenerhoff, Mark J.; Ton, Thai-Vu; Herbert, Ronald A.; Kissling, Grace E.; Hooth, Michelle J.; Behl, Mamta; Witt, Kristine L.; Smith-Roe, Stephanie L.; Sills, Robert C.; Pandiri, Arun R.
Rodent lung tumors are morphologically similar to a subtype of human lung adenocarcinomas. The objective of this study was to evaluate Kirsten rat sarcoma oncogene homolog ( Kras ), epidermal growth factor receptor ( Egfr ), and tumor protein 53 ( Tp53 ) mutations, which are relevant to human lung cancer, in cobalt metal dust (CMD)-induced alveolar/bronchiolar tumors of B6C3F1/N mice and F344/NTac rats. Kras mutations were detected in 67% (mice) and 31% (rats) of CMD-induced lung tumors and were predominantly exon 1 codon 12 G to T transversions (80% in mice and 57% in rats). Egfr mutations were detected in 17% (both mice and rats) of CMD-induced lung tumors and were predominantly in exon 20 with 50% G to A transitions (mice and rats). Tp53 mutations were detected in 19% (mice) and 23% (rats) of CMD-induced lung tumors and were predominant in exon 5 (mice, 69% transversions) and exon 6 (rats, all transitions). No mutations were observed for these genes in spontaneous lung tumors or normal lungs from untreated controls. Ames assay indicated that CMD is mutagenic in the absence but not in the presence of S9 mix. Thus, the mutation data (G to T transversions) and Ames assay results suggest that oxidative damage to DNA may be a contributing factor in CMD-induced pulmonary carcinogenesis in rodents.